Legislators' perceptions of unaccompanied children seeking asylum. Issue 4 (14th December 2015) - Hedlund, Daniel; Cederborg, Ann-Christin
Abstract : Purpose: – The purpose of this paper is to explore how individual legislators perceive unaccompanied minors seeking asylum, their life situation, needs and best interests. Design/methodology/approach: – The total number of participants were 15. Thematic analysis (Braun and Clarke, 2006) was used in order to identify and analyze patterns in the interview data. The authors focused on their responses to the questions about the best interest of the child in migration policy and practice, and how this principle was related to unaccompanied children seeking asylum. Findings: – The main finding is that chronological age becomes a key sign for how legislators understand the life situation, needs and best interests of unaccompanied children. Also, the findings from this study suggest that the moralizing welfare ideology of the past is still present in political discourse and social planning, construing unaccompanied minors as an ambivalent category between civilization and savagery. The findings from this study indicate that legislators enact reforms of importance for unaccompanied children without considering them as agents of their own future, with their own motives and reasons to seek asylum. Practical implications: – The findings from this study indicate a need to adapt the understanding of the existing Aliens Act (SFS 2005:716) to the knowledge that unaccompanied minors need to be assessed on their own terms. Originality/value: – This study contributes to increasing the understanding about how the subjective values of legislators may have influenced migration reform in Sweden that can be valuable to both legal and social research, as well as policy planners.